RESISTANCE OF FISHERMEN AND TOURIST PRACTITIONERS TO DEVELOPMENT OF CRAB, GROINT, AND WALK WAY ALONG BEACHES LOCATED IN SANUR AREA, DENPASAR, BALI - Winia, I Nyoman (E-Journal of Cultural Studies, 2015)
This study is to comprehend the resistance of fisherman community and tourism practitioner in the development of crab, groint, and walk way system in Sanur beach region, Denpasar, Bali. This research concerns on the real field with an emphirical character approach which relates to the resistance of fisherman community and tourism practitioner that is still highly  bubling. Lately, there has been an abrasion from the sea water which resulting to the damage of the coastal line structure. Results of the research indicated that: (1). The resistance of fisherman community and tourism practitioner in the development of crab, groint, and walk way system in Sanur beach has been meant as the occurrence of the conflict of interests between investors where the fisherman community and tourism practitioner are sacrified. (2). The causing factors of the resistance of fisherman community and tourism practitioner are due to the command for farm depletion in Sanur beach region by local government authority was without having a good socialization; the development of the tourism accommodation facilities by the investors exploited the farm of fisherman community and tourism practitioner; and also the loss occurred on the community members from the lateral impact incurred by the development of the crab, groint, and walk way system in Sanur beach region. (3). This community resistance has impacted the physical environment, social life, culture, and economy as well as the felt meaning in: the prosperity meaning, religion, politics and community psychology.
Keywords: resistance, community, investor, crab, groint, and walk way system.